Vulnerable Here or There? Examining the vulnerability of victims of human trafficking before and after return - Paasche, Erlend; Skilbrei, May-Len; Plambech, Sine (Anti-Trafficking Review, 2018)
This article deals with how return programmes for rejected asylum seekers and irregular migrants construct and create vulnerabilities. Few studies have explored the role of assistance provided through such programmes for the sex worker returnees and victims of trafficking who return through them. Even fewer holistically examine a return programme through data elicited in both destination and origin locations, before and after return. That is what we aim to do in this article. We first look at the legal-bureaucratic construction of vulnerability in a host state, Norway, and the systemic logic of its efforts to return victims of trafficking. We then look at how returnees narrate their experiences of and perspectives on vulnerability upon return to their country of origin, Nigeria. This study, together with the broader research within this field, indicates that flaws in programme implementation can in fact exacerbate vulnerabilities rather than help returnees overcome them.